2012
DOI: 10.1002/uog.11076
|View full text |Cite|
|
Sign up to set email alerts
|

Three‐dimensional Doppler evaluation of single spherical samples from the placenta: intra‐ and interobserver reliability

Abstract: Objective To evaluate the intra-and interobserver reliability of assessment of three-dimensional power Intra-and interobserver reliability was assessed by intraclass correlation coefficients (ICC).Results Ninety-five pregnancies were included in the analysis. All three placental 3D-PD indices showed only weak to moderate reliability (ICC < 0.66 and ICC < 0.48, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 35 publications
0
34
0
3
Order By: Relevance
“…Both Guiot et al and Lai et al showed poor inter-acquisition reliability when measuring VOCAL TM indices in samples when multiple areas of the placenta were compared, indicating regional variation in vascularity. 36,41 Another limitation is the use of a single acquirer for each patient and repeated sample acquisitions over the same VOI. Our findings support a study which demonstrated that within the placenta, distinct maternal vascular 'jets' arising from the basal plate project into the intervillous space, 24 leading to areas of mixed maternal and fetal pulsatility, reflected in lower absolute values for impedance indices.…”
Section: Discussionmentioning
confidence: 99%
“…Both Guiot et al and Lai et al showed poor inter-acquisition reliability when measuring VOCAL TM indices in samples when multiple areas of the placenta were compared, indicating regional variation in vascularity. 36,41 Another limitation is the use of a single acquirer for each patient and repeated sample acquisitions over the same VOI. Our findings support a study which demonstrated that within the placenta, distinct maternal vascular 'jets' arising from the basal plate project into the intervillous space, 24 leading to areas of mixed maternal and fetal pulsatility, reflected in lower absolute values for impedance indices.…”
Section: Discussionmentioning
confidence: 99%
“…Even worse, these indices are highly dependent on attenuation (Jones et al 2009;Miyague et al 2014;Raine-Fenning et al 2008a), which limits comparison between patients. Additionally, there are important concerns about reproducibility, particularly when the entire organ cannot be assessed and only a sample can be examined (i.e., the placenta from a third-trimester pregnancy) Martins et al , 2012; such variability could be explained by several factors including variability in movement, sampling region and even the phase in the cardiac cycle during 3-D-PD acquisition (Miyague et al 2013b). This approach is undergoing refinement with respect to 3-D-PD, particularly in the volumetric pulsatility index (Alcazar and Kudla 2012;Martins et al 2013;Welsh et al 2012b) and in fractional moving blood volume (Soares et al 2013;Welsh et al 2012a).…”
Section: Three-dimensional Power Doppler Ultrasoundmentioning
confidence: 99%
“…Three-dimensional (3D) power Doppler indices (vascularization index (VI), flow index (FI) and vascularization flow index (VFI)) have been shown to correlate with flow and vascularity 1 ; however, these indices are highly susceptible to machine settings and attenuation 2 . In this study, we sought to verify whether the volumetric pulsatility index (vPI) based on spatiotemporal image correlation (STIC) power Doppler 3 is less dependent on attenuation than the original 3D power Doppler indices obtained from both static 3D and STIC datasets by evaluating a flow phantom.…”
Section: Influence Of Attenuation On Three-dimensional Power Doppler mentioning
confidence: 99%